The Role of Open and Distance Learning in the Implementation of the Right to Education in Zambia - Siaciwena, Richard; Lubinda, Foster (International Review of Research in Open and Distributed Learning, 2008)
As a member of the United Nations, Zambia is committed to the observance of human rights enshrined in the Universal Declaration of Human Rights of 1948. This is evidenced, among others, by the fact that Zambia is a signatory to the Convention on the Rights of the Child and the African Charter on the Rights and Welfare of the Child. Zambia has a permanent Human Rights Commission that includes a subcommittee on child rights whose focus is on child abuse and education. Zambia also has a National Child Policy and National Youth Policy whose main objectives are to holistically address problems affecting children and youth. This paper focuses on the progress and challenges currently facing Zambia and the role of open and distance learning in addressing those challenges.